Contribution to the sustainable management of water and soil resources in North-West Benin: characterization of the watershed heads of the Ouémé and Pendjari rivers in the commune of Copargo - Kamarou Fare Kondo; Ibrahim Tchakala; Masamaéya Dadja-Toyou Gnazou; Sambienou Were Gedeon; Adandedji Firmin; Boukari Ousmane; Mama Daouda (European Scientific Journal, ESJ, 2024)
Due to their potential in ecosystem services, their wetlands and due to their lack of knowledge and their failure to take into account in the development and management plans of water and soil resources, the heads of watersheds for some time years undergo unprecedented anthropogenic pressure despite their fundamental role in determining the quantity and quality of the downstream watercourse. The present study was interested in shedding light on the characteristics as well as the issues associated with the watershed heads of the Ouémé and Pendjari rivers in the commune of Copargo. To achieve this objective, cartographic characterization techniques were implemented using mapping tools and the digital terrain model, followed by several exploratory analyzes using R software which made it possible to describe the variability of these areas. In Copargo, 25 watershed heads with similar operations and management issues were identified and delimited, including 14 in the Pendjari watershed and 11 in the Ouémé watershed. They occupy 59.4% of the surface area of the Pendjari watershed and 69% of the Ouémé watershed. Their surface area varies from 710ha to 4440ha with a compactness index of between 1.2 and 1.5. The slope varies from 1.5% to 4.5% and is more marked on the heads of small watershed areas. The headwater streams in the Copargo catchment represent 83.5% of the Ouémé river network and 85.7% of the Pendjari river network. Classifications based on morphology and land use profiles highlight groups characterized by vulnerability. This study will be followed by a physicochemical and bacteriological characterization study of water resources in the study area with a view to assessing the impact of anthropogenic pressure on them.